2021
DOI: 10.1159/000512456
|View full text |Cite
|
Sign up to set email alerts
|

A Short Cycle of Narrow-Band UVB Phototherapy in the Early Phase of Dupilumab Therapy Can Provide a Quicker Improvement of Severe Atopic Dermatitis

Abstract: <b><i>Background:</i></b> Since the best clinical response to dupilumab is achieved after 12–16 weeks, a combination therapy at the beginning of the treatment could be a helpful strategy to reach a faster response in patients with severe atopic dermatitis (AD). <b><i>Objectives:</i></b> To quantify the benefit of a combination of dupilumab treatment with a short course of narrow-band ultraviolet B (NB-UVB) phototherapy. <b><i>Methods:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Lipsky and German have recently determined the mechanical properties of isolated SC under UVR exposure and found that both UVA and UVB radiation cause mechanical and structural degradation [ 23 ]. Regardless of these harmful effects, UVB radiation was shown to have positive compensatory effects on the epidermal barrier when administered in low doses and over a relatively short period [ 24 , 25 ]. This therapeutic strategy is being used for the treatment of skin diseases with a disrupted epidermal barrier, such as atopic dermatitis, avoiding the possible side effects by applying only reduced intensity and exposure.…”
Section: Ultraviolet Radiation -Induced Photodamagementioning
confidence: 99%
“…Lipsky and German have recently determined the mechanical properties of isolated SC under UVR exposure and found that both UVA and UVB radiation cause mechanical and structural degradation [ 23 ]. Regardless of these harmful effects, UVB radiation was shown to have positive compensatory effects on the epidermal barrier when administered in low doses and over a relatively short period [ 24 , 25 ]. This therapeutic strategy is being used for the treatment of skin diseases with a disrupted epidermal barrier, such as atopic dermatitis, avoiding the possible side effects by applying only reduced intensity and exposure.…”
Section: Ultraviolet Radiation -Induced Photodamagementioning
confidence: 99%
“…However, after 12 and 16 weeks, the additional therapeutic effect of phototherapy diminished. 49 According to the current European guideline for the treatment of AD, children with moderate AD (SCORAD index can also be treated with narrowband UVB radiation. 50 The good efficacy of narrowband UVB therapy in children has been demonstrated in two clinical trials from India and England.…”
Section: Methodsmentioning
confidence: 99%
“…The combination therapy resulted in superior improvement in clinical lesions and symptom relief at 4 weeks. However, after 12 and 16 weeks, the additional therapeutic effect of phototherapy diminished 49 …”
Section: Physical Basicsmentioning
confidence: 98%
“…45 Laut der Leitlinie zur atopischen Dermatitis ist bei mittelschwerer atopischen Dermatitis UVA1 in mittlerer Dosierung ähnlich effektiv wie die Hochdosis UVA1 Strahlung. 46 49 Nach der aktuellen europäischen Leitlinie zur Behandlung der AD können auch Kinder mit moderater AD (SCORAD-Index 25-50) mit Schmalband UVB behandelt werden. 50 Die gute Wirksamkeit der Schmalband UVB Therapie bei Kindern konnte in zwei klinischen Studien aus Indien und England gezeigt werden.…”
Section: Phototherapie Der Atopischen Dermatitis (Ad)unclassified
“…Das kombinierte Schema führte zur stärkerer klinischer Verbesserung der Läsionen und Linderung der Symptome nach 4 Wochen. Nach 12 und 16 Wochen schwächte sich der zusätzliche therapeutische Effekt der Phototherapie jedoch ab 49 …”
Section: Introductionunclassified